Low-birth-weight scorecard for early prevention: the accuracy for predicting low-birth-weight infants based on maternal risk factor - Utami, Sri; Susilaningrum, Rekawati (Universitas Airlangga, 2024)
Introduction: Babies with low birth weight (LBW) have a risk of complications and health problems. One of the efforts to prevent LBW births is to detect risk factors in pregnant women. This study aimed to test the accuracy of an early LBW detection scorecard based on maternal risk factors. Methods: The research design used was observational analytical. The sample in this study was 177 mothers who were registered and delivered at hospitals and public health centers in Surabaya and were selected using a purposive sampling method. The research instruments used were LBW scorecard, maternal medical records, and baby's scale. The accuracy of the scorecard was measured with Mann-Whitney test, and Receiver Operating Characteristic (ROC) curve. Results: The LBW scorecard which was based on maternal factors analysis can significantly predict LBW births (p = 0.000). Based on the ROC curve analysis, it was known that the early detection scorecard has a cut-off point of 3.5, and an accuracy of 88.70%, which indicated that the scorecard has high accuracy in predicting LBW. Conclusions: The LBW early detection scorecards is able accurately to predict the incidence of LBW births. Through analysis and calculation of maternal risk factor, it can be seen whether the mother is at risk of giving birth to a LBW or normal weight baby. Early detection of LBW can improve services for at-risk babies, resulting in a positive impact on their health outcomes.